Forsøgs- og udviklingsarbejde i grundskolen som transgressiv praksis - Ydesen, Christian; Andreasen, Karen E. (Academic Quarter | Akademisk kvarter, 2011)
Much in the same spirit but with a broader focus Karen E. Andreasen and Christian Ydesen discuss the history of school education in Denmark in their article Forsøgs- og udviklings–arbejde i grundskolen som transgressiv praksis. Here, they show the historical development of transgressive practices in the Danish elementary school, revealing how government control alongside political currents shape these experiments as much as educators themselves.